Glycolysis – a key player in the inflammatory response - Soto‐Heredero, Gonzalo; Gómez de las Heras, Manuel M.; Gabandé‐Rodríguez, Enrique; Oller, Jorge; Mittelbrunn, María (The FEBS journal, 2020)
The inflammatory response involves the activation of several cell types to fight insults caused by a plethora of agents, and to maintain the tissue homoeostasis. On the one hand, cells involved in the pro‐inflammatory response, such as inflammatory M1 macrophages, Th1 and Th17 lymphocytes or activated microglia, must rapidly provide energy to fuel inflammation, which is essentially accomplished by glycolysis and high lactate production. On the other hand, regulatory T cells or M2 macrophages, which are involved in immune regulation and resolution of inflammation, preferentially use fatty acid oxidation through the TCA cycle as a main source for energy production. Here, we discuss the impact of glycolytic metabolism at the different steps of the inflammatory response. Finally, we review a wide variety of molecular mechanisms which could explain the relationship between glycolytic metabolites and the pro‐inflammatory phenotype, including signalling events, epigenetic remodelling, post‐transcriptional regulation and post‐translational modifications. Inflammatory processes are a common feature of many age‐associated diseases, such as cardiovascular and neurodegenerative disorders. The finding that immunometabolism could be a master regulator of inflammation broadens the avenue for treating inflammation‐related pathologies through the manipulation of the vascular and immune cell metabolism. Inflammatory cells switch their metabolism towards glycolysis to meet their high energetic and biosynthetic demand. Interestingly, metabolites that accumulate in glycolytic conditions have been described to reinforce the inflammatory response by modulating intracellular signalling pathways, remodelling the epigenetic landscape or regulating post‐transcriptional and post‐translational modifications. Regarding its impact on inflammation, the glycolytic metabolism of immune and vascular cells could be exploited to target inflammation‐associated pathologies.